Consolidated Report: KMD/ILRI OND 20204 Radio Talk Shows - Kenya Meteorological Department (KMD); International Livestock Research Institute (Kenya Meteorological Department (KMD), 2024)
ILRI supported Kenya Meteorological Department (KMD) for Radio talk shows for dissemination of OND 2024 seasonal Agro-weather advisories. The talk shows were County-based and used local FM stations. There were three talk shows (1-1 1.2 hr each) where County staff from KMD, Agriculture and livestock departments attended. The officers used the adverts to provide advisories to farmers within the County in relation to the OND2024 rainy Season.